Inside the Mind of the Turtles: How the World's Best Traders Master Risk - M. Faith Curtis (Mc Graw Hill, 2009)
Don't like uncertainty? Doubt makes you nervous? Most people are averse to it, but risk is unavoidable to the serious investor. In this groundbreaking book, Curtis Faith helps you not only form a truce with risk, but actually make it your ally.